ROLE OF INTRA CORONARY IMAGING AND PHYSIOLOGY IN DIAGNOSIS AND MANAGEMENT OF CORONARY ARTERY DISEASE - Parviz, Yasir; Awan, Kokab; Vijayan, Sethumadhavan; Sultan, Ayyaz; Iqbal, Javaid (Journal of Ayub Medical College Abbottabad, 2017)
Coronary artery disease (CAD) is the leading cause of death in the Indo-Pakistan subcontinent as well as globally. Coronary angiography is considered the gold standard test for the diagnosis of CAD. Therefore, an accurate interpretation of coronary angiography is of paramount importance in decision-making to treat patients with CAD. Coronary angiography has the inherent limitation of being a two-dimensional X-Ray lumenogram of a complex three-dimensional vascular structure. Visual assessment of angiogram can lead to both inter- and intra-observer variability in the assessment of the severity and extent of the disease which can lead to differences in management strategies. This issue becomes even more relevant when assessing left main stem (LMS), bifurcations, diffuse coronary artery disease or situations involving complex coronary morphology. Interventional cardiology has been revolutionised by recent advances in techniques, and innovative technologies in the catheterisation laboratory. Today, a modern catheterisation laboratory is equipped with adjunctive technologies, such as Quantitative Coronary Angiography (QCA), Fractional Flow Reserve (FFR), Intra-Vascular Ultra-Sonography (IVUS), and Optical Coherence Tomography (OCT), to help clinicians make a well-informed decision based on detailed anatomical and physiological assessment of a coronary artery rather than judgement based solely on visual assessment. In this article, we have briefly described the utility and evidence behind these adjunctive modalities and have provided examples of clinical cases to highlight their use in aiding physicians to make a well-informed treatment decision.